Method of Measuring Effective Dielectric Permittivity of Partially Filled Waveguides Using a Mismatched T-Bridge (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2019)
Introduction. Waveguides, partially filled with dielectric material (partially filled waveguides) are widely used in the super high frequency equipment. They have certain advantages over hollow waveguides, including the possibility of reducing sizes of a cross-section, increasing the power of radiation and suppressing undesired types of waves. Following the production of diverse new dielectric materials intended for use in super high frequency range devices, there is a need to continuously develop methods of calculation and measuring characteristics of partially filled waveguides.Statement of the problem. The theory of completely filled waveguides and waveguides with dielectric filling along narrow walls is developed quite thoroughly. However, its application to various waveguide devices requires the solution of transcendental equations, which is possible only using numerical methods. This makes it difficult to obtain information about any characteristics of a device. There is also an effect of a large number of factors influencing the characteristics of partially filled waveguides (degree of filling, position of a waveguide plate, magnitude of the dielectric permittivity, etc.). For the study of partially filled waveguides with different sample height, among others, this paper presents an approach, which is based on the representation of the relative permittivity of the medium in the form of two real functions, each of which depends on the cross-section from one coordinate. This is an approximate method for determining the proper scalar and vector functions of partially filled waveguides. The solution of the electrodynamic problem for partially filled waveguides is reduced to determining the propagation constant in a waveguide using exact or approximate methods. This paper presents the method which allows calculating the propagation constant at any frequency, by measuring the value of effective dielectric permittivity.Results and discussion. According to the results of the analysis, it is shown that known methods of measuring effective dielectric permittivity (using a measuring line, a panoramic indicator, and a bridge meter) have certain shortcomings in relation to the modification of partially filled waveguides, bandlimitedness, and a significant relative error of measurement with increasing effective dielectric permittivity. In particular, the lack of bridge meters is a very narrow frequency range in which the bridge remains matched. It is almost necessary to match the bridge at each frequency, reaching the absence of a signal in the arm E for identical loads that are connected to the side arm. For this, bridges have tuning elements in the form of pins, diaphragms, etc. The method for measuring effective dielectric permittivity of partially filled waveguides using an unmatched T-bridge, which does not have these deficiencies, is introduced.Conclusions. The scientific novelty of the proposed method for measuring effective permittivity of partially filled waveguides using an unmatched T-bridge is the possibility of providing broadbandness, increasing the accuracy of measurements, and the universality through the use of a panoramic indicator of the standing wave ratio using the voltage and electron-computer. One more point is the ability to measure effective dielectric permittivity when other measurement methods are not suitable. The results obtained should be used when designing new antenna systems, which include partly filled waveguides, as well as part of teaching and learning activities for creating new workplaces or improving existing ones aimed at laboratory and practical training using the above method of measurement.